A New CYP2E1 Inhibitor, 12-Imidazolyl-1-dodecanol, Represents a Potential Treatment for Hepatocellular Carcinoma. (2nd February 2021) - Diesinger, Torsten; Lautwein, Alfred; Bergler, Sebastian; Buckert, Dominik; Renz, Christian; Dvorsky, Radovan; Buko, Vyacheslav; Kirko, Siarhei; Schneider, Edith; Kuchenbauer, Florian; Kumar, Mukesh; Günes, Cagatay; et al.
Abstract : Cytochrome P450 2E1 (CYP2E1) is a key target protein in the development of alcoholic and nonalcoholic fatty liver disease (FLD). The pathophysiological correlate is the massive production of reactive oxygen species. The role of CYP2E1 in the development of hepatocellular carcinoma (HCC), the final complication of FLD, remains controversial. Specifically, CYP2E1 has not yet been defined as a molecular target for HCC therapy. In addition, a CYP2E1-specific drug has not been developed. We have already shown that our newly developed CYP2E1 inhibitor 12-imidazolyl-1-dodecanol (I-ol) was therapeutically effective against alcoholic and nonalcoholic steatohepatitis. In this study, we investigated the effect of I-ol on HCC tumorigenesis and whether I-ol could serve as a possible treatment option for terminal-stage FLD. I-ol exerted a very highly significant antitumour effect against hepatocellular HepG2 cells. Cell viability was reduced in a dose-dependent manner, with only the highest doses causing a cytotoxic effect associated with caspase 3/7 activation. Comparable results were obtained for the model colorectal adenocarcinoma cell line, DLD-1, whose tumorigenesis is also associated with CYP2E1. Transcriptome analyses showed a clear effect of I-ol on apoptosis and cell-cycle regulation, with the increased expression of p27Kip1 being particularly noticeable. These observations were confirmed at the protein level for HepG2 and DLD-1 cells grafted on a chorioallantoic membrane. Cell-cycle analysis showed a complete loss of proliferating cells with a simultaneous increase in S-phase arrest beginning at a threshold dose of 30 μ M. I-ol also reduced xenograft tumour growth in nude mice. This antitumour effect was not associated with tumour cachexia. I-ol was not toxic to healthy tissues or organs. This study demonstrates for the first time the therapeutic effect of the specific CYP2E1 inhibitor I-ol on the tumorigenesis of HCC. Our findings imply that I-ol can potentially be applied therapeutically on patients at the final stage of FLD.